Anton Kuh Biographie - Schübler, Walter (Wallstein Verlag, 2018)
Walter Schübler's biography paints a portrait of the extravagant bon vivant Anton Kuh with all his facets: the militant publicist, whose polemical squibs provided a running commentary to happenings in Vienna and Berlin, the alert chronicler of the 1910s, 20s and 30s, the avowed leftist, who risked his neck in conflicts with the Nazis, the oppositionist, who enjoyed teasing Karl Kraus, the bohemian, who took every chance to provoke, even when this was programmatically tactless, the neurasthenic with a self-destructive lifestyle, the phenomenal impromptu speaker, whose thoughts ran hot and whose audience responded with thunderous applause. The first biography of this »speech-actor« reconstructs the main body of Kuh's work - the impromptu speeches - and calls into question all of the rumors that are still circulating about this assumed »local hero«.